Access to grocery stores in Dallas. (2nd June 2008) - Berg, Nathan; Murdoch, James
This paper presents geo-spatial information concerning access to grocery stores in Dallas County, Texas. A map shows the spatial distribution of neighbourhoods classified according to the number of grocery stores within a one-mile radius. Neighbourhood-level data from the Texas Health and Human Services Commission and US Census reveal distinct demographic characteristics in areas with many versus few grocery stores. No-grocery-store neighbourhoods are predominantly low-income and concentrated in southern Dallas, and African-American neighbourhoods have significantly fewer grocery stores. Disparities in access to nutritious food suggest the possibility of a breakdown in food security, afflicting as many as 400, 000 low-income residents. The demographic correlates of grocery store access are analysed in light of economic and behavioural theories of consumer decisions about what to eat and firms' choices of where to locate stores.